Relationship between upper limb strength and forehand stroke outcomes in junior tennis players - Amanda, Rendy; Agust, Kristi; Lardika, Rola Angga (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: The performance of a tennis forehand stroke is influenced by several physical components, yet the specific contribution of hand muscle strength and arm power remains underexplored in junior athletes. Purpose: This study aims to determine the relationship between hand muscle strength and arm power with forehand stroke results in junior tennis athletes at the ATN Pekanbaru Club. Methods: A correlational research design with a survey method was employed. The population consisted of 13 junior athletes, and due to the small size, total sampling was applied. Instruments used included a handgrip dynamometer to measure hand muscle strength, a medicine ball put test to assess arm power, and a forehand accuracy test adapted from the physical test and tennis court guidebook. Data were analyzed using Pearson’s product moment correlation and multiple regression analysis. Results: Results showed a significant correlation between hand muscle strength and forehand results (r = 0.831), as well as between arm power and forehand results (r = 0.869), both exceeding the critical value r (0.5) (13) = 0.553. Simultaneously, both variables demonstrated a significant relationship with forehand performance (Fcount = 16.338 > Ftable = 4.103; r = 0.875). Conclusion: These findings suggest that hand muscle strength and arm power play critical roles in the effectiveness of forehand strokes in junior tennis athletes. However, the study is limited by its small sample size and focus on a single club. Future research should consider larger and more diverse samples while also examining additional biomechanical or technical factors to develop a more comprehensive model of junior tennis performance.